Cell-based artificial APC resistant to lentiviral transduction for efficient generation of CAR-T cells from various cell sources. Issue 2 (7th September 2020) - Schmidts, Andrea; Marsh, Leah C; Srivastava, Ambike A; Bouffard, Amanda A; Boroughs, Angela C; Scarfò, Irene; Larson, Rebecca C; Bedoya, Felipe; Choi, Bryan D; Frigault, Matthew J; Bailey, Stefanie R; Leick, Mark B; et al.
Abstract : Background: Adoptive cell therapy with chimeric antigen receptor T cells (CAR-T) has become a standard treatment for patients with certain aggressive B cell malignancies and holds promise to improve the care of patients suffering from numerous other cancers in the future. However, the high manufacturing cost of CAR-T cell therapies poses a major barrier to their broader clinical application. Among the key cost drivers of CAR-T production are single-use reagents for T cell activation and clinical-grade viral vector. The presence of variable amounts of contaminating monocytes in the starting material poses an additional challenge to CAR-T manufacturing, since they can impede T cell stimulation and transduction, resulting in manufacturing failure. Methods: We created K562-based artificial antigen-presenting cells (aAPC) with genetically encoded T cell stimulation and costimulation that represent an inexhaustible source for T cell activation. We additionally disrupted endogenous expression of the low-density lipoprotein receptor (LDLR) on these aAPC (aAPC-ΔLDLR) using CRISPR-Cas9 gene editing nucleases to prevent inadvertent lentiviral transduction and avoid the sink effect on viral vector during transduction. Using various T cell sources, we produced CD19-directed CAR-T cells via aAPC-ΔLDLR-based activation and tested their in vitro and in vivo antitumor potency against B cell malignancies. Results: We found that lack of LDLR expression on our aAPC-ΔLDLR conferred resistance to lentiviral transduction during CAR-T production. Using aAPC-ΔLDLR, we achieved efficient expansion of CAR-T cells even from unpurified starting material like peripheral blood mononuclear cells or unmanipulated leukapheresis product, containing substantial proportions of monocytes. CD19-directed CAR-T cells that we produced via aAPC-ΔLDLR-based expansion demonstrated potent antitumor responses in preclinical models of acute lymphoblastic leukemia and B-cell lymphoma. Conclusions: Our aAPC-ΔLDLR represent an attractive approach for manufacturing of lentivirally transduced T cells that may be simpler and more cost efficient than currently available methods.